Ethylene: Management and breeding for postharvest quality in vegetable crops. A review - Cocetta, Giacomo; Natalini, Alessandro (Frontiers in Plant Science, 2022)
Ethylene is a two-carbon gaseous plant growth regulator that affects growth, development, ripening and senescence of fruits, vegetables, and ornamental crops. At micromolar concentrations, the hormone accelerates ripening of ethylene sensitive leafy greens and vegetables and its accumulation can led to fruit decay and waste. Several strategies and techniques of plant breeding have been attempted in the last decades to understand ethylene regulation pathways and ethylene-dependent biochemical and physiological processes, with the final aim to extend and improve the postharvest quality of vegetables and ornamental crops. These investigation approaches include the use of conventional and new breeding techniques, including precise genome-editing. This review paper aims to provide a relevant state of the art related to the breeding for ethylene and ethylene-related metabolism, with a specific focus on the postharvest applications for vegetables and fruits. Moreover, some strategies related to the postharvest management of ethylene -sensitive species will be illustrated. An updated view and perspective on the implications of new breeding and management strategies to maintain the quality and the marketability of different crops during the postharvest are given, with particular focus on: - postharvest physiology (ethylene dependent) for mature and immature fruits and leafy vegetables. - postharvest quality management of vegetables: fresh and fresh cut products, focusing on the most important ethylene-dependent biochemical pathways; - evolution of breeding technologies for facing old and new challenges in postharvest quality of vegetable crops: from conventional breeding and marker assisted selection to new breeding technologies focusing on transgenesis and gene editing. Examples of applied breeding techniques for model plants (tomato) are given to elucidate ethylene metabolism, as well as beneficial and detrimental ethylene effects.